The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/09513590.2010.538101
|View full text |Cite
|
Sign up to set email alerts
|

Does nuchal translucency thickness in the first trimester predict GDM onset during pregnancy?

Abstract: NT thickness does not show a significative increase in those women who subsequently develop GDM. Therefore, NT assessment does not prove to be an useful ultrasound parameter for predicting GDM onset during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…34,35 Kelekci 12 found enlarged NT to be predictive of macrosomia in women with gestational diabetes, whereas two other studies did not. 36,37 The association between enlarged NT and macrosomia in non-diabetic pregnancies is thus far described by one large study 13 and confirmed by two smaller ones. 14,15 Poon 13 found a linear association between delta NT and birth weight, and delta NT was significantly larger in fetuses that were macrosomic at birth.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…34,35 Kelekci 12 found enlarged NT to be predictive of macrosomia in women with gestational diabetes, whereas two other studies did not. 36,37 The association between enlarged NT and macrosomia in non-diabetic pregnancies is thus far described by one large study 13 and confirmed by two smaller ones. 14,15 Poon 13 found a linear association between delta NT and birth weight, and delta NT was significantly larger in fetuses that were macrosomic at birth.…”
Section: Discussionmentioning
confidence: 75%
“…Some authors found lower PAPP‐A levels in case of maternal (gestational) diabetes but no association between NT and diabetes . Kelekci found enlarged NT to be predictive of macrosomia in women with gestational diabetes, whereas two other studies did not . The association between enlarged NT and macrosomia in non‐diabetic pregnancies is thus far described by one large study and confirmed by two smaller ones .…”
Section: Discussionmentioning
confidence: 95%
“…Luchi ve ark. İlk trimester NT ölçümünün GDM öngörüsündeki rolünü araştırmışlardır ve sonuçların kontrol grubundan farklı olmadığını görmüşlerdir [17]. Bizim çalışmamızda da NT değeri iki grup arasında benzer bulunmuştur.…”
Section: Discussionunclassified
“…La medida de la TN no parece asociarse al posterior desarrollo de DG 68,77 . Sin embargo, en fetos macrosómicos, la TN en el primer trimestre era mayor que en fetos con peso adecuado para la edad gestacional [71][72][73]75,76 .…”
Section: Marcadores Biofísicosunclassified